Pembiayaan Sindikasi Bank Syariah di Indonesia dalam Perspektif Hukum Ekonomi Syariah - Dery Ariswanto; Zedra Warang; Agung Wildan Azizi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
This article aims to describe and analyze the syndicated financing of Islamic Banks in Indonesia from the perspective of Islamic Economics Law. This study uses a qualitative research method with the type of library research used to analyze the formulation of the problem in this study. The results of this study indicate that the product innovation of Islamic banking can be carried out by applying a contract that is hybrid contract or multi-contract in nature. Sharia syndicated financing products emerge in the banking on the basis of the need for large amounts of financing, so that Islamic Banks will not be able to support it alone in other words, they must cooperate with other banks. Syndication financing is allowed based on the Fatwa DSN No: 91/DSN-MUI/IV/2014. Syndicated financing in Islamic Banks generally uses the musyarakah mutanaqishah contract. Syndicated financing in Islamic Banks has accommodated the provisions of both the Sharia Banking Law, KHES, Fatwa DSN, and other related regulations. So that the implementation of syndicated financing products at Islamic Banks in Indonesia is in principle aligned with Sharia Economic Law, however it must continue to be supervised by the Sharia Supervisory Board so that there are no violations of existing regulations.